Developing Muhammadiyah waqf lands through Islamic investment model: special case in Indonesia - Fahmi Medias; Zulfikar Bagus Pambuko; Chrisna Bagus Edhita Praja; Muhammad Ridhwan Ab. Aziz; Duddy Roesmara Donna (Varia Justicia, 2020)
Waqf institutions in some Muslim countries including Indonesia face obstacles in providing funds to manage their waqf lands. This paper aims to propose an alternative developing model for Muhammadiyah waqf institutions to meet the financing and management constraints using the concepts of waqf land categorisation using Islamic investment models. In this conceptual paper, the theory is used to propose a model for developing waqf Muhammadiyah in Indonesia. This study identified inefficiencies in managing Muhammadiyah waqf in Indonesia due to financial problems and the lack of ability of waqf institutions in developing assets. The authors have developed an investment model as a source of waqf land financing for Muhammadiyah waqf institutions in Indonesia. This model is expected to be a solution for empowering undeveloped and unproductive Muhammadiyah waqf lands and can be applied by Muhammadiyah waqf institutions in Indonesia. In the development of this study, Muhammadiyah waqf institutions, Islamic financial institutions, and policymakers will find alternatives in developing productive waqf for the ummah. The findings of this study will provide Muhammadiyah waqf institution with an Investment model to develop their waqf. Through this study, waqf will be useful in resolving the problems of poverty, unemployment, social inequality, improving education and health facilities, and improving the Indonesian economy. This model is different from the management of existing Muhammadiyah waqf, which is carried out consumptively. Then, waqf land that has been categorized is transformed into productive assets such as agricultural products and commercial business projects. The proposed investment model is to help Muhammadiyah waqf institutions to develop waqf land. The investment model is used to make Muhammadiyah waqf land more productive and play a role in social welfare.